Conceptualisations of poverty - Lars Engberg-Pedersen; Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2010)
Poverty reduction initiatives should be comprehensive, relational and global in their outlook even though poverty itself is always concrete and experienced in the local context. This is the major idea underlying this DIIS Report. The Report provides a brief overview of contemporary work on conceptualisations of poverty. It outlines characteristics of multi-dimensional and relational approaches to poverty and it examines the increased concern with the relation of inequality to poverty. The Report also touches upon current social, political and economic changes that have significant implications for poverty and the efforts to combat it. Finally, it indicates how different conceptualisations create different dilemmas for poverty reduction activities.
Keywords: 300; Armut; Soziale Ungleichheit; Sozialer Wandel; Entwicklung; Armutspolitik; Welt